2017
DOI: 10.5194/soil-3-161-2017
|View full text |Cite
|
Sign up to set email alerts
|

Potential short-term losses of N<sub>2</sub>O and N<sub>2</sub> from high concentrations of biogas digestate in arable soils

Abstract: Abstract. Biogas digestate (BD) is increasingly used as organic fertilizer, but has a high potential for NH 3 losses. Its proposed injection into soils as a countermeasure has been suggested to promote the generation of N 2 O, leading to a potential trade-off. Furthermore, the effect of high nutrient concentrations on N 2 losses as they may appear after injection of BD into soil has not yet been evaluated. Hence, we performed an incubation experiment with soil cores in a helium-oxygen atmosphere to examine the… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
19
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 47 publications
2
19
1
Order By: Relevance
“…Despite slightly different boundary conditions (different biogas digstate, slightly higher temperature with 15°C), a subsequent laboratory study by Fiedler et al. () showed higher N 2 O fluxes overall but compared to Gülzow significantly higher N 2 O fluxes again for the Dornburg soil cores. On the other hand, Heintze et al.…”
Section: Discussionmentioning
confidence: 92%
See 4 more Smart Citations
“…Despite slightly different boundary conditions (different biogas digstate, slightly higher temperature with 15°C), a subsequent laboratory study by Fiedler et al. () showed higher N 2 O fluxes overall but compared to Gülzow significantly higher N 2 O fluxes again for the Dornburg soil cores. On the other hand, Heintze et al.…”
Section: Discussionmentioning
confidence: 92%
“…Differences in N 2 O fluxes between the three related studies might be due to the well‐known spatial and temporal variability of N 2 O, particularly because samples were taken in different years and soil cores were treated differently [ i.e ., drying and rewetting for WFPS adjustment in Fiedler et al. ()]. However, N 2 fluxes from the BD treatment between the two subsequent studies were found to be similar for the two sites (Dornburg and Gülzow).…”
Section: Discussionmentioning
confidence: 96%
See 3 more Smart Citations